Untitled, watercolor on paper painting by Fernand Léger, 1921, Honolulu... - Fernand Léger (Wikimedia Commons, 1921)
Notice iconographique issue de Wikimedia Commons. Titre: Untitled, watercolor on paper painting by Fernand Léger, 1921, Honolulu Museum of Art. Untitled, watercolor on paper painting by Fernand Léger, 1921, Honolulu Museum of Art.
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons